CONFLICT MANAGEMENT IN LONG DISTANCE MARRIAGE COUPLES FROM A FAMILY COUNSELING PERSPECTIVE (CASE STUDY OF LDM PAIRS IN COMBAT ENGINEER BATALYON 18/YUDHA KARYA RAKSAKA): PENGELOLAAN KONFLIK PADA PASANGAN PERNIKAHAN JARAK JAUH DALAM PERSPEKTIF KONSELING KELUARGA (STUDI KASUS PASANGAN LDM DI BATALYON ZENI TEMPUR 18/YUDHA KARYA RAKSAKA) - SYAHBILLA Pristiwana; Siti Napisah; Ratna Wulandari (Program Studi Bimbingan dan Konseling, 2025)
This research was conducted to find out how married couples who are in a long distance relationship are tested and required to have a high level of trust in their partner and what steps and solutions must be taken for married couples who are in a long distance relationship to be tested and required to have a high level of trust. This research uses a qualitative descriptive approach method with the aim of understanding each couple in depth and detail, because the qualitative method directly meets and interviews 2 married couples totaling 4 subjects with structured interviews. The data collection techniques used are interviews, documentation, observations. Researchers use data analysis, namely data reduction, data presentation and conclusions. In the relationship between TNI couples who experience LDM because the task carried out by the husband requires the couple to undergo an LDM relationship and the intensity of meeting is also very long. Besides, the condition of the communication that is established is often neglected, making the situation in the couple's relationship have to foster a sense of trust so that household conditions continue to work. well without causing prolonged conflict.